Smart City: An Approach from the View of Smart Urban Governance - NGO, Hung Viet; LE, Quan (International Journal of Sustainable Construction Engineering and Technology, 2021)
The worldâ€™s population is forecasted of having 68% to be urban residents by 2050 while urbanization in the world continues to grow. Along with that phenomenon, there is a global trend towards the creation of smart cities in many countries. Looking at the overview of studies and reports on smart cities, it can be seen that the concept of â€œsmart cityâ€ is not clearly defined. Information and communication technology have often been being recognized by the vast majority of agencies, authorities and people when thinking about smart city but the meaning of smart city goes beyond that. Smart city concept should come with the emphasizing on the role of social resources and smart urban governance in the management of urban issues. Therefore, the "smart city" label should refer to the capacity of smart people and smart officials who create smart urban governance solutions for urban problems. The autonomy in smart cities allows its members (whether individuals or the community in general) of the city to participate in governance and management of the city and become active users and that is the picture of e-democracy. E-democracy makes it easier for stakeholders to become more involved in government work and fosters effective governance by using the IT platform of smart city. This approach will be discussed more in this paper.